2018
DOI: 10.1007/s40843-018-9308-7
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-bandgap Nb2O5 nanowires with enclosed pores as high-performance photocatalyst

Abstract: Porous niobium oxide nanowires synthesized via a solvothermal method exhibited decreased bandgap, enhanced light absorption and reduced charge-recombination rate. The porous Nb 2 O 5 nanowires showed increased performance for the photocatalytic H 2 evolution and photodegradation of rhodamine B, as compared to their solid counterparts, which could be ascribed to the peculiar porous nanostructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In summary, the previous prepared Nb2O5 was thermally treated in an aluminum reduction device, where the sample and aluminum powder were positioned independently in a two- Clearly, such morphological and structural transformations lead to changes in the optical and electronic properties of niobium oxide. In this sense, Zhang et al reported an enclosed porous structure of pseudo-hexagonal tief-tief (TT) Nb 2 O 5 nanowires, which showed a significant decrease in the band gap from 3.22 to 2.95 eV in relation to the nonporous Nb 2 O 5 nanowires, and then an enhancement of H 2 eVolution under visible light irradiation (λ > 420 nm) [25]. The material was prepared by a solvothermal synthesis using ammonium niobate(V) oxalate hydrate and oleic acid mixed with trioctylamine.…”
Section: Niobium Pentoxide (Nb 2 O 5 )mentioning
confidence: 99%
“…In summary, the previous prepared Nb2O5 was thermally treated in an aluminum reduction device, where the sample and aluminum powder were positioned independently in a two- Clearly, such morphological and structural transformations lead to changes in the optical and electronic properties of niobium oxide. In this sense, Zhang et al reported an enclosed porous structure of pseudo-hexagonal tief-tief (TT) Nb 2 O 5 nanowires, which showed a significant decrease in the band gap from 3.22 to 2.95 eV in relation to the nonporous Nb 2 O 5 nanowires, and then an enhancement of H 2 eVolution under visible light irradiation (λ > 420 nm) [25]. The material was prepared by a solvothermal synthesis using ammonium niobate(V) oxalate hydrate and oleic acid mixed with trioctylamine.…”
Section: Niobium Pentoxide (Nb 2 O 5 )mentioning
confidence: 99%
“…The wet chemistry typically uses the surfactants to modify the lattice topology and surface for realizing the site‐selective growth of one material onto another, but inevitably creates abundant grain boundaries of weak interfacial adhesion and thereby weak charge‐transfer capability. [ 8 ] Epitaxial growth of materials can more readily give high‐quality heterostructures (e.g., ZnO/BiOI, [ 9 ] Fe 2 O 3 /CuO, [ 10 ] Co III ‐MOF/Co II ‐MOF, [ 11 ] and 1D NiZn‐LDH/2D NiZn‐LDH [ 12 ] ) when the components have suitable crystal structures and orientation that can engage in lattice matching. Despite these advances, lattice mismatch can still occur during crystal growth to create randomly aggregated rather than ordered heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic features of mesoporous materials such as nanoconnement effects, high adsorption capacities, and exceptional optical and electronic properties have led to broad potential applications in batteries, 8,9 energy conversion and storage, [10][11][12] various areas of catalysis, [13][14][15] and photocatalysis. [16][17][18][19] In this context, photocatalysis is one of the promising approaches to meet the increasing energy demands as well as to address the growing environmental contaminations, [20][21][22][23][24][25] in which semiconductors play a central role in determining the overall performance. [26][27][28][29] At this juncture, Nb 2 O 5 represents a highly favored semiconductor with superior redox properties, plentiful polymorphs, excellent chemical stability, and abundant acid sites.…”
Section: Introductionmentioning
confidence: 99%